Structural improvement for stabilization of photochemical hydrogen doping in ZnO thin film - Kim, Jinseo; Duy, Le Thai; Park, Ayoung; Park, Jucheol; Seo, Hyungtak (Journal of Alloys and Compounds, 2019)
ZnO, a cost-effective metal-oxide semiconductor, has received many attentions for sensing and optoelectronic applications. To improve its properties for developing practical applications, our study on investigating effects of H-doping with UV photochemistry on ZnO thin films, especially electrical property, was presented with the use of a thin film transistor (TFT) platform. Here, ZnO thin films, used as the active channel, were deposited by radio frequency plasma sputtering at room temperature. For an investigation of structural effect, post-deposition annealing (PDA) was carried out before UV irradiation used to introduce H species. By combining these two processes, a significant improvement of the electrical property of ZnO based TFTs, due to the crystallization enhancement along with an increase of doping level, was observed and discussed in detail. Overall, our approach was simple but effective to tune properties of oxide semiconductors.
Keywords: Metal oxide semiconductor; Optoelectronic applications; Post deposition annealing; Property control; Radio frequency plasma; Structural improvements; UV irradiation; ZnO films; Post-deposition annealing (PDA); Property control; TFT; UV irradiation; ZnO film